Improving the Students’ Creative Thinking using Problem Based Worksheet on the Topic of Environmetal Pollution - Sri Lestari, Ni Wayan Nila; Fadiawati, Noor; Jalmo, Tri (Jurnal Pendidikan Progresif, 2018)
Improving the students’ creative thinking skills using problem based worksheet on the topic of environmental pollution. Objectives: This research aims to investigate the effectiveness of problem based worksheet to improve students’ creative thinking skills on the topic of environmental pollution.Methods: Creative thinking skills were measured using four indicators: fluency, flexibility, originality, and elaboration. The research was designed using the matching only pretestpostest control group design. The data of creative thinking skills were collected from pretest and posttest and analyzed using statistical analysis such as normality, homogeneity, t-test, and Mann-Whitney test. Findings: Students’ elaboration skill showed the highest improvement related to the effect size (0.92) and n-gain value (0.73). Conclusion: The problem based worksheet is effective to improve students’ creative thinking skill.Keywords: Worksheet, problem based learning, creative thinking skill. DOI: http://dx.doi.org/10.23960/jpp.v8.i2.201814